(3ebGdI aj WHY GScfOQjIs - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s
(3ChdgG (B:s
(3bGd CjOc Gddg ef JThbc Edi eYQaI WHY GdCScfOQjI hMGd ghGFgG heGFgG hfMh Pdc ef CMhGdgG s
(3BNQgG (B:s
(3hPcQfG CeKdI Pdc hEfg jfHZi Cf jSJYed ai eYGdLJgG HGdCOhjI GdbhejI JeJ GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs